The Isolation and Genome Sequencing of Five Novel Bacteriophages From the Rumen Active Against Butyrivibrio fibrisolvens - Friedersdorff, Jessica C. A.; Kingston-Smith, Alison H.; Pachebat, Justin A.; Cookson, Alan R.; Rooke, David; Creevey, Christopher J. (Frontiers in Microbiology, 2020)
Although the prokaryotic communities of the rumen microbiome are being uncovered through genome sequencing, little is known about the resident viral populations. Whilst temperate phages can be predicted as integrated prophages when analysing bacterial and archaeal genomes, the genetics underpinning lytic phages remain poorly characterised. To the five genomes of bacteriophages isolated from rumen-associated samples sequenced and analysed previously, this study adds a further five novel genomes and predictions gleaned from them to further the understanding of the rumen phage population. Lytic bacteriophages isolated from fresh ovine and bovine faecal and rumen fluid samples were active against the predominant fibrolytic ruminal bacterium Butyrivibrio fibrisolvens. The double stranded DNA genomes were sequenced and reconstructed into single circular complete contigs. Based on sequence similarity and genome distances, the five phages represent four species from three separate genera, consisting of: 1) Butyrivibrio phages Arian and Bo-Finn; 2) Butyrivibrio phages Idris and Arawn and 3) Butyrivibrio phage Ceridwen. They were predicted to all belong to the Siphoviridae family, based on evidence in the genomes such as size, the presence of the tail morphogenesis module, genes that share similarity to those in other siphovirus isolates and phylogenetic analysis using phage proteomes. Yet, phylogenomic analysis and sequence similarity of the entire phage genomes revealed that these five phages are unique and novel. These phages have only been observed undergoing the lytic lifecycle, but there is evidence in the genomes of phages Arawn and Idris for the potential to be temperate. However, there is no evidence in the genome of the bacterial host Butyrivibrio fibrisolvens of prophage genes or genes that share similarity with the phage genomes.